Tear Film Instability and Meibomian Gland Dysfunction Correlate with the Pterygium Size and Thickness Pre- and Postexcision in Patients with Pterygium - Li, Ning (J Ophthalmol, 2019)
PURPOSE: This study aimed to evaluate the effects of excision on dry eye and meibomian gland dysfunction (MGD) in individuals with pterygium, before and after surgery. It also aimed to investigate how these effects correlate with the size and thickness of the pterygium. SUBJECTS AND METHODS: 63 eyes from 63 patients with primary nasal pterygium and 45 eyes from 45 healthy volunteers without ocular pathologies were enrolled in this study. 63 eyes from 63 patients underwent pterygium surgery. ImageJ software was used to calculate the pterygium size based on images of the anterior segments. Anterior segment spectral domain optical coherence tomography (SD-OCT) was performed preoperatively to measure the thickness of the pterygium 1 mm anterior to the nasal scleral spur. The ocular surface disease index (OSDI), Schirmer I Test (SIT), and MGD grade were used to evaluate the eyes, and the eyes were imaged using the noninvasive keratograph average tear film breakup time (NIBUTav), tear meniscus height (TMH), meiboscore, and lipid layer grading tools of the Oculus® Keratograph 5M, preoperatively and at 1, 3, and 6 months postoperatively. RESULTS: The OSDI, NIBUTav, lid margin abnormality, meiboscore, and lipid layer grading values differed significantly in the pterygium patients in comparison with the controls (p < 0.01 for all scores). However, the SIT and TMH values were unchanged between the two groups (all p > 0.05). Multivariate regression analysis demonstrated that the NIBUTav, meiboscore, and lipid layer grading score was significantly correlated with the pterygium parameters, such as size and thickness. The postoperative OSDI, NIBUTav, lid margin abnormality, and lipid layer grading values improved significantly (p < 0.05 for all scores). The SIT, TMH, and meiboscore results did not differ significantly between the pre- and postoperative values (p > 0.05). Among the conventional and automated indexes, at 1 month postoperatively, SIT and TMH were significantly correlated with the pterygium parameters, but no correlation was observed at 3 and 6 months postoperatively. The OSDI, NIBUTav, meiboscore, and lipid layer grading values at 1, 3, and 6 months postoperatively were significantly correlated with the pterygium parameters. CONCLUSION: Abnormal tear film and meibomian gland (MG) function improved following pterygium excision in the patients with primary pterygium, which was associated with uncomfortable ocular symptoms. Pterygium parameters, such as size and thickness, correlated with the dry eye and MGD indexes in patients pre- and postoperatively, potentially offering a novel strategy for clinical implementation of pterygium excision surgery.